Metabolic threshold defined by disproportionate increases in physiological parameters: A meta-analytic review - Wyatt, F. B.; Jackson, C. G.; Tran, Z. V. (Medicine & Science in Sports & Exercise, 1997)
Anaerobic threshold is defined as a point just prior to metabolic acidosis where blood lactate concentrations and associated gas exchange variables change in a disproportionate manner. The use of the term "anaerobic threshold" may be erroneous. Studies (N = 61) which met inclusion criteria, revealed 17 different "thresholds" which were related to the metabolic processes involved with anaerobic threshold. Factor analysis showed that disproportionate changes were the result of increased work intensity and metabolic rate. Wide variations in specific threshold variables (lactate, ventilatory, work output, catecholamine, respiratory exchange ratio, heart rate) indicate inflections are influenced more by glycolytic rate than anaerobic conditions. This quantitative analytic review suggests that disproportionate changes in physiological variables, formerly used to describe anaerobic threshold, more appropriately define a metabolic threshold. Implication. The concept of anaerobic threshold and its being caused by a few processes is not supported. The body has a variety of response mechanisms, many of which are redundant, with which to cope with exercise stress. However, an individual reacts to increased workload that produces a level of metabolic demand through increased glycolysis that induces fatigue at an accelerated rate. This appears to be better described as the "inflection point of metabolic acceleration." That point is best described as a particular level of work intensity for a particular activity. It is specific to each activity and will vary between trained and untrained states. No specific and limited physiological test is adequate for measuring this phenomenon. "Anaerobic threshold" is an inappropriate term.